Free radial artery forearm flap reconstruction of forehead defect in a 2-year-old child - Balan, Jyoshid R.; Roy, Vinu; Gopal, Raj; K., Pradeep Kumar; S., Ajai K. (International Surgery Journal, 2021)
Reconstruction of soft tissue defect with exposed bone over the forehead is a technical challenge in pediatric population. The options vary from skin grafting, local flaps to complex microvascular tissue transfer. The local flaps leave unsightly scar in the neighboring area and may violate the hair bearing scalp, hair line and the direction of hair. Skin grafting requires a vascular bed for its take and the aesthetic appearance is inferior. The tissue expansion in an acute stage may not be an option. Here we present our experience of soft tissue reconstruction of a forehead defect in a 2-year-old child with free radial forearm flap (RAFF). To best of our knowledge free radial forearm flap has rarely been reported for usage in reconstruction of forehead defect in pediatric population.